Welcome to Me [videorecording (DVD)] - Wiig, Kristen, 1973-; Cardellini, Linda, 1975-; Cusack, Joan, 1962-; Marsden, James, 1973- (Millennium Entertainment, 2015)
A year in the life of Alice Klieg, a woman with Borderline Personality Disorder who wins Mega-millions, quits her meds and buys her own talk show.